Comprehensive dosimetric comparison of halcyon 3.0 versus truebeam for breast cancer volumetric modulated arc therapy plans - Gu, Anyan; Wang, Mengyuan; Pan, Zhenyu; Tang, Ran; Li, Yaotao; Wu, Yu; Yang, Guozi; Sun, Xingru (Frontiers in Oncology, 2025)
BackgroundBreast cancer is the foremost malignancy threatening female health. This study aimed to compare the dosimetric performance of Halcyon 3.0 and TrueBeam in Volumetric Modulated Arc Therapy (VMAT) planning for breast cancer.MethodsThirty post-operative breast cancer patients were included. VMAT plans for Halcyon 3.0 and TrueBeam were generated using 6MV FFF beams in Eclipse 16.1 with identical optimizing objectives. Organs At Risk (OARs) and target metrics were evaluated. Statistical analysis employed paired t-tests or Wilcoxon signed-rank tests (α=0.05).ResultsHalcyon significantly reduced the mean dose of heart (Δ = −112.5 cGy, P< 0.001), left anterior descending artery mean dose (Δ = −151.3 cGy, P< 0.001), and spinal cord maximum dose (Δ = −88.2 cGy, P = 0.011). Low-dose exposure improved, with heart V5 (volume receiving ≥500 cGy) reduced from 22.0% to 12.6% (P< 0.001) and ipsilateral lung V5 reduced from 59.4% to 45.8% (P< 0.001) between Halcyon and TrueBeam. Halcyon lowered the absolute volume received 500 cGy by 487 cm³ (P< 0.001). Halcyon had the better target homogeneity (homogeneity index: Δ = -0.01, P< 0.001), while conformity remained comparable (P > 0.05). Despite having higher monitor units (Δ = 87.5, P< 0.001), Halcyon maintained delivery efficiency through faster leaf motion speed and gantry rotation velocity.ConclusionsCompared with TrueBeam, Halcyon achieved reduction in low-dose exposure while maintaining target coverage in breast cancer VMAT planning, thereby lowering radiation doses to OARs (e.g., heart and lung V5). This benefit is likely attributed to Halcyon’s unique staggered dual-layer MLC design.